HUBUNGAN KEBISINGAN LALU LINTAS UDARA (PESAWAT UDARA) DENGAN GANGGUAN PROSES PEMBELAJARAN DI SMA NEGERI 3 KOTA BENGKULU - Mualim, Mualim (Jurnal Sanitasi Profesional Indonesia, 2023)
Noise is unwanted sound that can cause hearing loss. The level of air traffic noise (aircraft) and room temperature at SMAN 3 Bengkulu City exceeds the NAV of 81.3 dB. The research objective was to determine the relationship between air traffic noise levels (aircraft) with the disruption of the learning process of students of SMAN 3 Bengkulu City. The observational research method with a cross-sectional study population approach was all students of SMAN 3 Bengkulu City as many as 856 students, the sample of the study was a portion of the students from each representative as many as 90 students were taken using proportional random sample. The results showed that the level of aircraft noise with the learning process of SMAN 3 students in Bengkulu City (ρ = 0,000). The conclusion is that there is a relationship between aircraft noise level and the learning process of students of SMAN 3 Bengkulu City. Suggestions for schools to control noise by planting Kalpataru trees, installing silencers (fibers or foam).